2015
DOI: 10.1007/s11065-015-9302-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis

Abstract: Parkinson's disease (PD) is a common, degenerative disorder of the central nervous system. Individuals experience predominantly extrapyramidal symptoms including resting tremor, rigidity, bradykinesia, gait abnormalities, cognitive impairment, depression, and neurobehavioral concerns. Cognitive impairments associated with PD are diverse, including difficulty with attention, processing speed, executive functioning, memory recall, visuospatial functions, word-retrieval, and naming. Deep brain stimulation (DBS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
152
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(170 citation statements)
references
References 56 publications
12
152
1
Order By: Relevance
“…One critical area of post-DBS outcomes that was not addressed by our study was cognition. While many have studied the effects on specific DBS targets on cognitive outcomes,36 there have been no studies of anaesthetic technique on short-term or long-term cognitive outcomes after DBS. Finally, meta-analysis results are always limited by the quality of the data reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…One critical area of post-DBS outcomes that was not addressed by our study was cognition. While many have studied the effects on specific DBS targets on cognitive outcomes,36 there have been no studies of anaesthetic technique on short-term or long-term cognitive outcomes after DBS. Finally, meta-analysis results are always limited by the quality of the data reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to such a concept, the latter might account for the present findings. In general, DBS of the STN seems to be more susceptible to changes in cognitive scores compared to DBS of the GPi, although it has been stated that the particular influences of stimulation, trajectory, and lead placement still need to be disentangled [63]. …”
Section: Discussionmentioning
confidence: 99%
“…This article expands upon previous finding reporting the outcome of the open-label randomized controlled trial of a constant current DBS device which found improvements in patient reported good quality "on" time compared to a delayed stimulation control group (3). The new study (2) supplements the former limited neuropsychological data presented (3), and examines the cause and impact of verbal fluency declines following surgery, which is the most consistent and persistent cognitive decline reported in DBS patients (4).…”
mentioning
confidence: 98%
“…To date, current controlled stimulation has not been evaluated in GPi DBS, which according to a recent meta-analysis 4 may be a safer surgical alternative to STN in terms of its neurocognitive and neurobehavioral profile. The metaanalysis revealed that STN DBS led to cognitive declines in more domains than was found for studies investigating GPi DBS, and a greater reduction in depression symptomatology following GPi versus STN.…”
mentioning
confidence: 99%